Opportunities for the Progression of Farm Animal Welfare in China - Sinclair, Michelle; Lee, Hui Pin; Chen, Maria; Li, Xiaofei; Mi, Jiandui; Chen, Siyu; Marchant, Jeremy N. (Frontiers in Animal Science, 2022)
As the world’s largest livestock producer, China has made some progress to improve farm animal welfare in recent years. Recognizing the importance of locally-led initiatives, this study aimed to engage the knowledge and perspectives of Chinese leaders in order to identify opportunities to further improve farm animal welfare in China. A team of Chinese field researchers engaged 100 senior stakeholders in the agriculture sector (livestock business leaders, agriculture strategists and intellectuals, government representatives, licenced veterinarians, agriculture lawyers and national animal welfare advocates). Participants completed a Chinese questionnaire hosted on a national platform. The raw data responses were then translated and subjected to qualitative and quantitative analysis from which themes were built and resulting recommendations were made. The findings of this study urge emphasis on the ties between improved animal welfare with food safety, product quality and profit, and demonstrate the existence of animal welfare opportunities outside of the immediate introduction of specific animal protection legislation. The resulting applications are anticipated to be of strategic use to stakeholders interested in improving farm animal welfare in China.